Knowledge on Varicose Vein among Security Guards Working in a Selected Hospital, at Mangaluru - Ramyashree, S.; Lobo, Asha; Varghese, Jisha; Baby, Nimisha; Varghese, Soumya (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of the study was to create an awareness of varicose veins among security guards. Background: Varicose veins are swollen, twisted, and sometimes painful veins that have filled with an abnormal collection of blood which is commonly seen in workers who does their job for standing longtime. Methodology: A descriptive cross-sectional study was done among 73 security guards working in a specialized hospital using nonprobability purposive sampling using a valid structured knowledge questionnaire. Results: In this study, majority of the subjects (46.6%) were in the age group of 41 years’, majority (83.6%) were standing during work, and working hours is 98.6%. The computed P values of the baseline variable, posture during work (χ² =6.075; P = 0.048*). Whereas, the baseline variable such as age (χ² = 7.085; P = 0.131), sex (χ² = 0.313; P = 0.576), education(χ² = 6.140; P = 0.105), experience (χ² = 2.825; P = 0.244), total hours of working (χ² = 1.485; P = 0.233), duration of standing (χ² = 1.562; P = 0.668), shift changes (χ² = 4.930; P = 0.085), and previous knowledge (χ² = 1.485; P = 0.223) is more than 0.05 level of significance. Conclusion: The duties and responsibilities of security guards are different in different areas. The result of this study helped to provide general information about varicose veins among security guards which will give baseline knowledge to the health professionals so they can suggest good health practices and promote good general health.